A split-face of dermaroller and intradermal injection with the autologous platelet rich fibrin lysate in the treatment of exogenous ocronosis: A case series - Mochtar, Moerbono; Ilona, Sri Esa; Zulfikar, Dendy; Murastami, Ammarilis; Widhiati, Suci (Dermatology Reports, 2019)
Exogenous ochronosis (EO) is a rare, cosmetically disfiguring condition, resulting from the long term use of topical hydroquinone in treatment of melasma. The studies about it are small and many of the treatments have mixed result. Autologous human platelet rich fibrin (PRF-L) is contains platelet that are purpose to release numerous growth factor that valuable in numerous dermatologic application.Platelet rich fibrin lysate used for EO has not been reported. We presented three cases with EO treated with split-face of the PRF-L applied right before dermaroller on right face and intradermal injection on the left for 8 weeks.The treatment re-apply every 2 weeks. The improvement was measuring by 10-point grading scale and dermoscopic examination, including five-point grading scale to assessment of patient satisfaction. All of three patients demonstrated significant improvementand very satisfied in 4th week of treatment. This result suggests that PRF-L can be used as of one modality for EO treatment.